Empowering a Rural Highland Community in Getasan District through Black Soldier Fly-Based Organic Waste Management for a Circular Economy Transition - Heriyanti, Andhina Putri; Febriyanto, Hendra; Mustikaningtyas, Dewi; Kholil, Putri Alifa; Fariz, Trida Ridho; Salsabilla, Nur Hayati Afrilda; Romadhon, Vhaviriele Abel; Haris, Amnan (Unram Journal of Community Service, 2025)
Waste management in Indonesia is still dominated by open burning and landfilling, causing environmental and health problems. In Jetak Village, Getasan District, Semarang Regency, located in the rural highlands of Mount Merbabu, organic waste dominates household waste streams. Although a TPS3R facility has existed since 2022, its operation remains suboptimal due to low community participation and odor issues. This condition highlights the urgent need for innovative, community-based solutions. Black Soldier Fly (BSF, Hermetia illucens) farming offers an effective alternative, capable of reducing organic waste by 50–60% while producing valuable by-products. This community service program targeted village officials, farmer groups, women’s groups, youth, and TPS3R managers. Activities included awareness sessions on circular economy, training in BSF cultivation, field demonstrations using appropriate technology, digital marketing workshops, and operational assistance at TPS3R. Impact was assessed through participant questionnaires and scenario modeling of household-level BSF adoption based on waste generation data from SIPSN (2025) and BPS (2025). Twenty-five participants engaged actively throughout the program. Evaluation showed 100% agreement that BSF is effective for organic waste management, with 89% willing to adopt it at home. Products such as fresh and dried larvae and frass were successfully introduced, with estimated market value up to IDR 52,000/kg. Scenario analysis indicated potential reductions of 89–268 tons of organic waste annually and mitigation of 2.6–7.8 tons CO₂e, depending on adoption rates. The program proved that BSF technology is feasible, socially acceptable with proper education, and economically promising. It strengthened local waste management capacity, supported income generation, and contributed to circular economy transition while aligning with SDG 12 and Indonesia’s low-carbon development goals.